Determinantes del uso de la inteligencia artificial en la enseñanza universitaria: un enfoque cualitativo - Guerrero López, Carlos Alberto (2024)
This study explores the perception of some university professors regarding the integration of artificial intelligence (AI) in higher education teaching. Using a qualitative approach, fifty professors from various disciplines were carefully selected and interviewed to obtain their perspectives on the impact of AI in the educational field. The professors responded to a semi-structured questionnaire covering six key aspects: their general perception of AI in education, the use of AI-based tools, perceived benefits, concerns, recommendations for successful implementation, and the future vision of AI’s role in higher education. The data obtained show a positive attitude towards AI, highlighting its potential to personalize learning, automate repetitive tasks, and improve educational efficiency. However, concerns also emerged, such as the privacy of students’ data, the cost of accessing AI with better tools, and the risk of dehumanizing the educational process. Respondents emphasized the importance of a gradual implementation, combining technology with human interaction, and ensuring adequate training for teachers and students. This study contributes to the understanding of how AI can be effectively integrated into university teaching, providing a foundation for future research and educational practices. It concludes that AI has the potential to significantly transform higher education, as long as it is handled with care and responsibility.